Enhancement of three isolation optimizations by more reliable estimation of seismic action predominant period - Morales, César A. (2024)
As a large base displacement level is the main drawback of the generally very successful seismic isolation technique, latest optimization procedures for the subsystem at base are focused on the control of that displacement. One family of procedures is based on the existence of one predominant frequency in earthquake excitation, which is evident only if the spectral analysis is performed considering displacement as the input, rather than the common ground acceleration. Nevertheless, recent results, besides corroborating the existence of one predominant period, have produced an improvement in the computation of this single spectral parameter. In this paper, this more reliable seismic predominant frequency is employed in previously successful methodologies to control isolator displacement. The hypothesis is that an enhanced model of the input will result in an improved structural response, which again, it is further reduced base displacements.